REFLEXIVE - IMPORTANCE AND STAGES OF INNOVATIVE TECHNOLOGIES IN TEACHER ACTIVITY - To‘xtayeva Zebo Sharifovna; Rahmatova Barnogul Karimjonovna (American Journals, 2024)
This article identifies the most important factors for improving the effectiveness of innovative activities and identifies the stages of adopting new ideas in pedagogical processes, identifying and solving problems, introducing innovations in reflexive innovative practice, and also emphasizes the importance of psychological training and adoption of pedagogical innovations to prepare teachers for innovative activities. The article outlines practical approaches to increasing the exchange of information and experience between teachers and students by creating an innovative environment and creating a creative environment, developing strategies for preparing teachers for innovative activities and introducing innovations in general, creating the necessary conditions for stimulating innovative activities in education.
Keywords: Innovative activity, pedagogical process, new ideas, problem solving, reflexive innovative practice, innovation, stages, preparation of teachers for innovative activities, psychological training, pedagogical innovations.